Samsung Electronics [M] Sdn. Bhd / Nurul Ain Mawaddah Jamahari - Jamahari, Nurul Ain Mawaddah (2022)
Samsung Electronics (M) SDN BHD is an international brand company that established in Malaysia since 1989. In this company analysis, it is focusing on the Family Hub Smart Fridge that is produced by Samsung Electronics to be investigate, identified and analysed along with their current difficulties and come out with solutions. Samsung Family Hub is an internet of Things-enabled refrigerator with a massive touch screen that brings refrigerators into the future. Acting as a giant tablet attached to your refrigerator door, it features a voice-controlled assistant named Bixby that recognizes individual voices and provides personalized information for each member of the family. The first problem regarding their product is the fridge is lack of lighting. Lighting is one of the importance things that refrigerator should have. Without good and enough lighting make it hard to see what inside the fridge especially at night. As for the next problem, the fridge has very heavy door to open. These problems could be disadvantages for the oldster who had less energy compares to youngster when open the fridge door. Aside from that, there are a few solutions to that problems primarily are do innovation, research and development. New alternative can be done such as placing the lighting on the strategic places that can light all the fridge. The next solution is, with new innovations using voice-controlled to open and closed the fridge as the automatic options aside from manual opening options.